2021
DOI: 10.1590/1414-431x2021e11396
|View full text |Cite
|
Sign up to set email alerts
|

De novo ALX4 variant detected in child with non-syndromic craniosynostosis

Abstract: Current understanding of the genetic factors contributing to the etiology of non-syndromic craniosynostosis (NSC) remains scarce. The present work investigated the presence of variants in ALX4, EFNA4, and TWIST1 genes in children with NSC to verify if variants within these genes may contribute to the occurrence of these abnormal phenotypes. A total of 101 children (aged 45.07 ± 40.94 months) with NSC participated in this cross-sectional study. Parents and siblings of the probands were invited to participate. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…This variant was found in one patient with unilateral coronal suture synostosis, and segregation analysis showed an incompletely penetrant phenotype in the parents of the proband [ 22 ]. Subsequent studies identified the EFNA4 variant (c.178C > T, p.His60Tyr) in three additional patients with nonsyndromic, single suture synostosis ( Supplementary Figure S2 ) [ 23 , 24 ]. Functional analysis by Merill et al demonstrated that this variant results in a 65% loss of the binding of ephrin-A4 proteins to EphA7, the partner receptor, by disrupting the formation of the ligand–receptor heterotetramer [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This variant was found in one patient with unilateral coronal suture synostosis, and segregation analysis showed an incompletely penetrant phenotype in the parents of the proband [ 22 ]. Subsequent studies identified the EFNA4 variant (c.178C > T, p.His60Tyr) in three additional patients with nonsyndromic, single suture synostosis ( Supplementary Figure S2 ) [ 23 , 24 ]. Functional analysis by Merill et al demonstrated that this variant results in a 65% loss of the binding of ephrin-A4 proteins to EphA7, the partner receptor, by disrupting the formation of the ligand–receptor heterotetramer [ 22 ].…”
Section: Discussionmentioning
confidence: 99%